The attitude toward self-esteem and the perceptions of resiliency among female prostitutes within the City of Manila - Barcelona, Jhazmine E. 4 0 16; 5 (2018)
ABSTRACT: The purpose of this study is to know the attitudes on self-esteem and perceptions of reliency among female prostitutes. The researcher developed guide questions for interview in gathering information from 15 female prostitutes with the City of Manila. The data were collected by using the semi-structured, face-to-face type of interview. The participants were able to answer the questions in line with the objectives of this study and were able to share their life experiences. Using phenomenological approach and thematic analysis, the researcher analysed and interpreted the findings. The researcher found out that female prostitutes attitude about self-esteem can be positive or negative depending to what factor influences them most. Culture, social contructs, gender roles, and past experiences have a lot of effect into the attitudes on self-esteem. Under the positive attitude, it can be viewed collectively or individually. In collectively, it includes valuing for women and the human beings as a whole. In individualistic approach, there were self-trust, self-care, self-worth. In the negative attitude the themes were forgetting oneself, self-despair, and self-despondency or hopelessness. In resiliency, the perceptions of resiliency were having faith in God, self-perseverance, overcoming life challenges, hope, standing one one's own, becoming a fighter, and awareness of responsibilities.
Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2